Pengaruh Kepercayaan, Motivasi, Dan Pelayanan Terhadap Tingkat Kepuasan Nasabah PT. Bank Mandiri Taspen Kc Medan - Sagala, Kevin Yosua Orlando; Mirza, Deni Faisal; Sinaga, Estetika Debora; Fauzi, Fauzi; Mirza, Muhammad Fadlan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The objective of this research is to analyze the influence of Trust, Motivation, and Service on Customer Satisfaction both partially and simultaneously. The research method used in this study is quantitative. The population of this study comprises 10,597 customers, with a sample size of 100 customers. The sampling technique used is random sampling, and data collection methods include questionnaires and interviews. The data analysis technique employed is multiple linear regression analysis. The study results show that the calculated t-value for trust is greater than the critical t-value and the significance value is less than 0.05, specifically, tcount>ttablet_count > t_tabletcount?>ttable? and sig.<0.05sig. < 0.05sig.<0.05 or 0.291<1.9850.291 < 1.9850.291<1.985 and 0.772>0.050.772 > 0.050.772>0.05. This indicates that trust does not have a significant partial effect on customer satisfaction. The calculated t-value for motivation is greater than the critical t-value and the significance value is less than 0.05, specifically, tcount>ttablet_count > t_tabletcount?>ttable? and sig.<0.05sig. < 0.05sig.<0.05 or 2.402>1.9852.402 > 1.9852.402>1.985 and 0.018<0.050.018 < 0.050.018<0.05. This indicates that motivation has a significant partial effect on customer satisfaction. The calculated t-value for service is greater than the critical t-value and the significance value is less than 0.05, specifically, tcount>ttablet_count > t_tabletcount?>ttable? and sig.<0.05sig. < 0.05sig.<0.05 or 2.770>1.9852.770 > 1.9852.770>1.985 and 0.007<0.050.007 < 0.050.007<0.05. This indicates that service has a significant partial effect on customer satisfaction. The study results show that the calculated F-value is greater than the critical F-value and the significance value is less than 0.05, specifically, Fcount>FtableF_count > F_tableFcount?>Ftable? and sig.<0.05sig. < 0.05sig.<0.05. The values obtained from data processing are F=8.534>2.70F = 8.534 > 2.70F=8.534>2.70 and sig.=0.000<0.05sig. = 0.000 < 0.05sig.=0.000<0.05. This indicates that trust, motivation, and service have a positive and significant effect on customer satisfaction. The determination coefficient test results show that 18.6% of customer satisfaction is influenced by trust, motivation, and service, as indicated by the Adjusted R Square value. The remaining 81.4% is explained by other variables not examined in this study.